Stem cell in urology—are we at the cusp of a new era? - Panda, Arabind (Translational Andrology and Urology, 2018)
Stem cell therapy can potentially disrupt conventional medicine as we practice it today. Stem cells can self-renew and differentiate and by this, repair and in certain conditions regenerate damaged tissue. In the past two decades, there has been significant research into its value in several chronic urological conditions for which conventional therapy is unsatisfactory. Stem cell therapy has been tried on animal models of bladder dysfunction, stress urinary incontinence (SUI), erectile dysfunction and urethral injury and certain preclinical studies have had very encouraging results. Yet despite this explosion of knowledge about the nature and value of stem cells, translation of research into the clinical domain has been slow. In addition, lack of regulation of stem cell therapy has resulted in indiscriminate, unscientific administration of stem cell therapy to patients. This review looks into the advances in the use of stem cells in urological practice, the recent regulatory guidelines that have been introduced and what the future holds for this exciting branch.